AGE, BODY MASS INDEX, BODY COMPOSITION IN POSTMENOPAUSAL WOMEN WITH CHRONIC VENOUS DISEASE - Povoroznyuk, V.V.; Kostromin, G.O.; Zaverukha, N.V.; Chebotarev, D.F. (World of Medicine and Biology, 2020)
Chronic venous disease (CVD) is one of the common, though controversial problems in modern medicine. The aim of our study is to determine the association between age, body composition, obesity and CVD in postmenopausal women. We have examined 96 postmenopausal women aged 46-85 years (mean age – 66.19±0.96 years), that in accordance to the presence of CVD all women were divided in two groups. The diagnosis of CVD was established on C-category of clinical, anatomical and pathophysiological (CEAP) classification and vascular surgeon consultation. We have detected increases of CVD frequency with age in postmenopausal women (from 72 % in those aged 45-59 years to 84 % in those aged 75-89 years). A significant correlation between the total fat mass and age was determined in postmenopausal women with CVD. Significantly, higher values of body weight, BMI, total body fat, and lower extremity body fat were found in the oldest group with CVD compared to patients without CVD.
Keywords: chronic venous disease; risk factors; age; obesity; postmenopausal women